Hydrothermal Synthesis and Crystal Structure of a New Co(II) Coordination Polymer With One-Dimensional Helical Chains. Issue 9 (1st September 2016) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract : A new Co(II) coordination polymer, [Co(bda)(bpa)]n (1 ) [H2 bda = 4, 4′- benzophenonedicarboxylic acid and bpa = bis(4-pyridyl)amiine], has been prepared by hydrothermal synthesis and characterized by IR, X-ray diffraction, and elemental analysis. Complex [Co(bda)(bpa)]n (1 ), triclinic system, space group P -1 with a = 12.015(5) Å, b = 13.195(5) Å, c = 16.922(5) Å, α = 104.801(5)°, β = 90.028(5)°, γ = 116.953(5)°, V = 2290.9(15) Å 3, Z = 2, Mr = 498.35, Dc = 1.445 g/cm 3, F (000) = 1020, and µ = 0.791 mm −1 . The final refinement gave R = 0.0360and wR = 0.0450 for 8127 reflections with I > 2σ( I ). X-ray diffraction analysis reveals that complex1 shows a two-dimensional layer structure with one-dimensional helical chains.